Advances of nanomaterials‐based strategies for fighting against COVID‐19. Issue 4 (5th May 2021) - Zeng, Chunxi; Hou, Xucheng; Bohmer, Margaret; Dong, Yizhou
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has infected over 100 million people globally due to its high infectivity. After decades of efforts on the studies of nanomaterials, researchers have applied nanomaterials‐based strategies to combat the pandemic of the coronavirus disease 2019 (COVID‐19). First, nanomaterials facilitate the development of easy, fast, and low‐cost diagnostic assays to detect SARS‐CoV‐2 and related biomarkers. Second, nanomaterials enable the efficient delivery of viral antigens to antigen‐presenting cells or serve as adjuvants in the host, leading to vaccine development at an unprecedented pace. Lastly, nanomaterials‐based treatments may inhibit SARS‐CoV‐2 replication and reduce inflammation. Overall, nanomaterials have played important roles in controlling this COVID‐19 pandemic. Here, we provide a brief overview of the representative examples of nanomaterials‐based diagnostics, vaccines, and therapeutics in the fight against COVID‐19. Abstract : The COVID‐19 pandemic has infected millions and millions of people worldwide. This mini‐review summarizes the nanomaterial‐enabled applications for COVID‐19 diagnostics, vaccines, and therapeutics.